Ceftriaxone-induced immune hemolytic anemia: a case report - Wang, Li; Jiang, Yongxian; Li, Gen; Zhang, Liaoyun; Qin, Bo; Li, Aiyan (Frontiers in Immunology, 2025)
BackgroundDrug-induced immune hemolytic anemia (DIIHA) is a rare but serious disease associated with various antibiotics, which is often misdiagnosed. DIIHA often leads to adverse outcomes, including organ failure and even death. Ceftriaxone is one of the most common drugs that cause DIIHA. This study reports a case of ceftriaxone-induced DIIHA.Case descriptionA 5-year-old patient diagnosed with community-acquired pneumonia developed a rash on the 5th day of anti-infective treatment with cefazoxime and azithromycin, followed by a rapid decline in hemoglobin levels and the presence of hemoglobin in the urine (hemoglobinuria). Laboratory analysis showed a positive Coombs’ test for the patient. The rash and hematuria subsided after cefazoxime and azithromycin were stopped and symptomatic treatment such as methylprednisolone intravenous infusion, sodium bicarbonate-alkalized urine, enoxaparin sodium anticoagulation, and antiallergic therapy. 5 days later, the child was treated with ceftriaxone for anti-infective therapy because the pneumonia was not healed. During the treatment, the patient suddenly developed itching all over the body, pale face, slightly fast breathing, vomiting, abdominal pain, and low back pain. Immediate cessation of ceftriaxone sodium infusion, continuous nasal catheter oxygen inhalation, normal saline dilatation, and meprednisolone anti-inflammatory and symptomatic treatment of cetirizine were performed. On the evening of the same day, the patient presented with symptoms of wine-colored urine. Laboratory analysis indicated severe anemia and persistent hemolysis, which was considered to autoimmune hemolytic anemia caused by ceftriaxone. After three transfusions and plasma exchange, the patient improved and was discharged from the hospital. One month later, there were no obvious abnormalities in urine analysis, blood routine analysis, reticulocyte analysis, and liver function test.ConclusionUnderstanding the patient’s medical history can provide critical information for the diagnosis of DIIHA, and effective management of DIIHA includes immediate discontinuation of suspected drugs, transfusion support, plasma exchange, and symptomatic medication.